Penggunaan Terapi Komplementer dalam Modern Wound Dressing pada Pasien dengan Luka Diabetes: Literature Review - Hesti Kusumastuty; Nur Setiawati Dewi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: The number of diabetes mellitus sufferers with diabetic ulcus continues to increase. Wound care using conventional methods is no longer effective. Selection of the right wound care can effectively improve wound healing and reduce the financial burden on serving the clientst. The aim of this literature review was to explore the efficacy of wound healing with modern wound care management in diabetic ulcers. Methods: A literature search using the Google Scholar database, Springer Link, Clinical Key, Pubmed and Proquest found 20 journal articles that match the criteria. Results: The majority of research results show the effectiveness of using modern clothing to heal diabetic wounds. Conclusion: Modern wound care dressings with the addition of complementary therapies have shown a more significant effect in accelerating diabetic wound healing.